A COMPARATIVE REVIEW OF SURETY BONDS & TENDER BIDDING: IN QUEBEC (INCLUDING NUNAVIK), NEWFOUNDLAND (INCLUDING NUNATSIAVUT), AND NUNAVUT (Canadian Journal of Native Studies, 2026)
AbstractThis paper is a comparative exploration of approaches to tender biddingand surety bond use in three Canadian jurisdictions: the Provinceof Quebec, as Canada’s sole civil law jurisdiction; the common-law jurisdictionof the north-easterly neighboring Province of Newfoundlandand Labrador; and, to the north of Quebec, Canada’s newest territorialgovernment, Nunavut. The review will also include an examinationof the Indigenous self-governing regions of northern Quebec, Nunavikand northern Newfoundland and Labrador, Nunatsiavut.The research commences with a literature review and discussion ofthe early history of contract law and the principle of good faith, as well asa review of the historical timeline and evolution of the use of suretyshipvia surety and other forms of bonds. From the completion of the historicalreview of tender bidding and surety bonds, the focus of the papershifts to examining their use within public procurement policies withrespect to contracts at the federal level, along with the select provincial,territorial and Indigenous governments. This paper also examines therespective self-government agreements and “land claim agreements,” toascertain the tendering flexibility and surety bond requirements.This project’s research methodology uses secondary data such aslegal studies and case commentaries, as well as relevant political scienceand sociological papers, along with credible news articles and governmentwebpages. This paper’s research also includes communicationwith the administrations of the National Aboriginal Capital Corporations’Association (NACCA), the Territorial Government of Nunavut,the Nunavik regional government and the government of Nunatsiavut.